Induction of cross-neutralizing antibody against H5N1 virus after vaccination with seasonal influenza vaccine in COPD patients - Uraiwan Kositanont (2018)
Archival serum samples from elderly individuals with underlying chronic obstructive pulmonary disease (COPD) who were enrolled in a double-blind case-control study of seasonal influenza vaccine efficacy were assayed for cross-neutralizing antibody formation to avian influenza A (H5N1) virus. Of 118 serum samples, 58 were collected from influenza vaccinees (mean age 68.5y), and 60 from placebo controls (mean age 68.4y) who received vitamin B injections. Blood samples were collected before and at 1mo after seasonal influenza vaccination from all subjects; in addition, for a longitudinal follow-up period of 1y paired-blood samples were collected again from subjects who developed acute respiratory illness. Hemagglutination inhibition assay for antibodies to influenza A (H1N1), influenza A (H3N2), and influenza B viruses was carried out to determine the serological response to vaccination, and to diagnose influenza viral infection, while microneutralization assays were performed to detect cross-reactive antibody to H5N1 virus. Pre-existing cross-reactive H5N1 antibody at reciprocal titer 10 was found in 6 (10.3%) vaccinees and 4 (6.7%) placebo controls. There was no change in H5N1 antibody titer in these subjects after vaccination. On the other hand, 3 (5.2%) vaccinees developed seroconversion to H5N1 virus at 1mo after vaccination, even though they had no pre-existing H5N1 antibody in their first blood samples. No cross-neutralizing antibody to H5N1 virus was detected in the placebo controls or in the 22 influenza patients, suggesting that influenza vaccination, but not influenza virus infection, induces cross-neutralizing antibody against avian influenza H5N1 virus. © 2010, Mary Ann Liebert, Inc.